Dam failure and a catastrophic flood in the Mekong basin (Bolaven Plateau), southern Laos, 2018 - Latrubesse, Edgardo Manuel (2021)
Sudden breaching of a saddle dam on July 23, 2018, on the perimeter of the Xe Nammoy hydroelectric-power reservoir, recently constructed in the Mekong basin, southern Laos, caused catastrophic flooding that resulted in fatalities and displaced thousands of individuals. This study aims to (1) assess the cause of the dam breach, and (2) understand the hydrologic and geomorphic impact of the flood. Our analysis shows that the collapse of the dam occurred as the reservoir was nearly full, and the water level was rising against the inner slope of the earthen dam. As the water discharged through the breach, we calculate that the reservoir fell ~22 m and lost ~350 million m3, more than a third of the total stored volume on July 23. Inspection of publicly available photographs of the failed dam confirms our interpretation that the failure was structural, involving both piping and rotational slumping, and not due to overtopping of the dam. Failure to properly process the local materials before construction of the earth-core of the dam is the likely cause of failure. Our analysis of satellite imagery, bolstered by field observations, reveals that the flooding inundated an area of ~46 km2 of villages and rural land in the Vang Ngao River, a tributary of the Mekong River basin. By using 1D and 2D hydrological modeling, we calculate a peak flood discharge of ~8500 m3/s, about half the mean discharge of the Mississippi River. The dam failure and concomitant losses are consistent with common inadequacies in this region in assessing potential hazards, challenges of geomorphological-geotechnical engineering when using tropical materials for construction, and emergency planning and warning. Thus, this analysis has important implications for the safer design and construction of the myriad of other dams that are either operating or planned within the multi-national Mekong River basin.